Assessing the short-to medium-term supply risks of clean energy minerals for China. (1st April 2019) - Zhou, Yanjing; Li, Jianwu; Wang, Gaoshang; Chen, Shouyu; Xing, Wanli; Li, Tianjiao
Abstract: Concerns about both climate change and energy security stress the importance of clean energy technologies. This paper examines the minerals used in clean energy technologies (mainly solar energy, wind energy and electric vehicles), of which 12 elements are identified to be dependent on resources outside China. Therefore, a quantitative, relative assessment of short-to medium-term supply risks is measured for 12 elements by analyzing the following factors: country concentration, import reliance, import concentration, country risk, depletion time, companion metal fraction, recycling potential and substitutability. The results highlight four elements to present a high risk, namely: tin, cobalt, chromium and nickel; while lithium, copper and titanium are the most impossible to encounter a supply disruption; the remaining five elements (silver, cadmium, zirconium, manganese and selenium) appear a moderate risk. An uncertainty analysis using Monte Carlo simulation shows a robust reliability on most of the 12 elements except for cobalt and tin. Mitigation strategies to alleviate the potential supply disruption are also discussed, such as broadening import sources; investing domestic and global mining; recycling and substitution; stockpiling. Highlights: Concerns of climate and energy crisis stress the importance of clean technologies. Supply risks associated with clean energy minerals for China are assessed. Nine supply risk indicators are used to evaluate twelve elements. Sn, Co, Cr and Ni are shown higher supply risks than the other 8 elements. Some suggestions to alleviate supply risks are discussed.